Hippocampal and motor fronto-cortical neuroligin1 is increased in an animal model of depression. (30th September 2016) - Feng, Pingfu; Akladious, Afaf A.; Hu, Yufen
Abstract: Neuroligins (NLGNs) regulate synaptic excitability, neuronal signaling and sleep. We hypothesize that alteration of NLGNs is involved in the pathology of depression and tested the hypothesis in a model of depression using Wistar Kyoto (WKy) rat and its control, the Wistar (Wis) rat. We first evaluated behavioral deficits using the forced swim test and then characterized alterations of NLGN1 and NLGN2 with RT-PCR and Western Blotting in the prefrontal cortex, motor frontal cortex and hippocampus. Compared with controls of Wis rats, (1) the WKy rats had significantly shorter swim time and longer immobile time; (2) NLGN1 mRNA levels was higher in the motor frontal cortex and hippocampus in the WKy model; (3) NLGN1 protein was significantly higher in the motor frontal cortex, the prefrontal cortex and the hippocampus in the WKy model; (4) NLGN2 mRNA was significantly higher in the motor frontal cortex but significantly lower in the hippocampus in the WKy model. We concluded that NLGN1 gene and protein expression is higher in the motor frontal cortex, hippocampus and in the prefrontal cortex in the WKy rats suggesting that alterations of NLGN1 is involved in the pathology of depression but need to be further evaluated in human. Highlights: The rat model of depression, WKy rat, had significantly longer immobile time. NLGN1 mRNA levels was higher in the frontal cortex and hippocampus in the WKy Rat. NLGN1 protein was significantly higher in all 3 brain regions in the WKy model. NLGN2 mRNA was higher in the frontal cortex but lower in the hippocampus in the WKy model.